(5R*,11R*)-5-Methyl-1,2-dihydro-5,11-methano-5H,11H-1,3-thiazolo[2,3-d][1,3,5]benzoxadiazocine - Viktor Kettmann; Jan Světlík; Lucia Veizerová (Acta Crystallographica Section E, 2009)
The title compound, C13H14N2OS, crystallizes as a racemate in a non-chiral space group. It represents a conformationally restricted analogue of so-called Biginelli compounds known to exhibit multiple pharmacological activities and was selected for a single-crystal X-ray analysis in order to probe the chemical and spatial requirements of some kinds of activity. It was found that the state of hybridization of the formally aminic nitrogen of the heterocycle is between sp2 and sp3 with the lone-pair electrons partially delocalized through conjugation with the sulfur atom rather than the double bond of the pyrimidine nucleus. As a result, the thiazolo ring adopts a flat-envelope conformation and the puckering of the central pyrimidine ring is close to a half-chair. The critical phenyl ring is fixed in a pseudo-axial and perpendicular [dihedral angle 84.6 (1)°] orientation with respect to the pyrimidine ring via an oxygen bridge.